BUFFALO PRODUCTION AND RESEARCH IN INDONESIA: Obstacles and Opportunities - Yasin, Suhubdy (Proceeding Buffalo International Conference, 2013)
Buffalo is one of large ruminants playing pivotal roles in supporting the daily life and socio-economy of the Indonesian farmers. They primary utilize them as draft animal, meat and milk production, supporting some momentous religion and cultural obligations. Buffalo is mostly raised under traditional management systems with no special attention or treatment has been given to their feeding, breeding, reproduction, and health systems.Â Â  Buffalo is a unique animal and they can still survive and reproduce even while consuming low quality roughage and living in harsh ecological condition. Presently, there is a limited scientific data and information has been published in relation to factors affecting the husbandry and distinctiveness of Indonesian buffalo. This paper firstly reviews and elucidates the current progress and obstacles of buffalo production. Then the research progress, opportunity and challenge for buffalo developments are outlined; and ultimately, considerable developmental strategies are formulated in order to improve the quantity and quality of Indonesian buffaloes.